The beginning of the scientific work of Kiev University Professor G.N. Minch - Ruda, S. P. (History of science and technology, 2013)
The article is devoted to one of the founders of the pathologic anatomy in Russia in the XIXth century. – G. N. Minch, who made a significant contribution to the studying of the etiology of infectious diseases. In the focus of attention is early work of the scientist associated with the work in St. Catherine Hospital and his participation in physical and mathematical society.